Mechanisms of gastro-oesophageal reflux in cystic fibrosis. Issue 5 (May 1991) - Cucchiara, S; Santamaria, F; Andreotti, M R; Minella, R; Ercolini, P; Oggero, V; de Ritis, G
Abstract : Abnormal degrees of gastro-oesophageal reflux (GOR) were detected by 24 hour intraoesophageal pH measurement in 12 of 14 children (mean age 7.9 years; range 5 months-16 years) affected by cystic fibrosis and complaining of symptoms suggesting GOR. These patients underwent combined recording of distal oesophageal motility and intraluminal pH in order to investigate mechanisms of GOR. Inappropriate lower oesophageal sphincter relaxation was the most common mechanism of reflux in all patients. Other mechanisms (appropriate relaxation or lowered pressure of the lower oesophageal sphincter, increased intragastric pressure) were detected less frequently. Frequency of inappropriate lower oesophageal sphincter relaxations was significantly higher in patients with cystic fibrosis than in other study groups (symptomatic GOR, GOR disease complicated by respiratory complaints). Inappropriate lower oesophageal sphincter relaxations occurred with the same frequency in patients with cystic fibrosis and in a group of children with GOR disease complicated by oesophagitis. Abnormalities of distal oesophageal contractions such as decreased amplitude or uncoordinated waves were also recorded in cystic fibrosis patients. Seven patients with cystic fibrosis completed a therapeutic trial for eight weeks consisting of postural treatment and oral cisapride, a new prokinetic drug. The oesophageal acid exposure improved in only three patients. We conclude that pathologic GOR is commonly associated with cystic fibrosis. The predominant reflux mechanism in these patients is a transient inappropriate lower oesophageal sphincter relaxation rather than a low steady state basal lower oesophageal sphincter pressure.